2021
DOI: 10.1016/j.gore.2021.100777
|View full text |Cite
|
Sign up to set email alerts
|

Tracing ovarian cancer research in Morocco: A bibliometric analysis

Abstract: Highlights Research on ovarian cancer in Morocco seems to be neglected. Nearly all publications were dominated by case reports and case series on rare ovarian tumors. There is an urgent need for studies on ovarian cancer in all fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…1 Our recent bibliometric analysis of ovarian cancer research in Morocco has highlighted numerous issues in terms of clinical research focusing on this particularly aggressive form of women’s cancer. 2 Indeed, the findings of our study have shown that there is no original research on ovarian cancer. Instead, the majority of the analyzed literature consists of low-impact case reports, lacking a substantial impact on patient care or health policy development.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…1 Our recent bibliometric analysis of ovarian cancer research in Morocco has highlighted numerous issues in terms of clinical research focusing on this particularly aggressive form of women’s cancer. 2 Indeed, the findings of our study have shown that there is no original research on ovarian cancer. Instead, the majority of the analyzed literature consists of low-impact case reports, lacking a substantial impact on patient care or health policy development.…”
mentioning
confidence: 70%
“…Instead, the majority of the analyzed literature consists of low-impact case reports, lacking a substantial impact on patient care or health policy development. 2 Overall, this scarcity of research in the epidemiological, clinical, and pathological aspects of ovarian cancer in Morocco can be attributed to factors common in resource-limited countries, including insufficient funding, inadequate training for healthcare professionals in conducting clinical research, and a lack of research initiatives in gynecologic oncology.…”
mentioning
confidence: 99%
“…It is emphasized that this research included studies focused on EOC, not ovarian cancer in general and exosomes alone, not microvesicles and extracellular vesicles. There are several bibliometric reviews on different aspects of ovarian cancer ( Wang et al, 2016 ; El Bairi et al, 2021 ; Gupta et al, 2021 ; Khedkar et al, 2021 ; Liu et al, 2022 ; Xu and Li, 2022 ) but there is no bibliometric review on EOC and applications of exosomes in EOC. The analysis of productivity by year showed that despite the growth of research interest in exosomes in different fields, research on exosomes and EOC has opened up in recent decades, and it is in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology allows not only the evaluation of research quality but also the identification of developing research trends and the prediction of possible future research directions ( 11 , 12 ). Previous studies have utilized bibliometric analysis to examine prominent research topics and studies concerning OC ( 13 15 ). Duan’s research revealed that platinum-resistant OC is primarily focused on identifying populations that can benefit from immunotherapy alongside the practical implementation of immune checkpoint inhibitors ( 13 ).…”
Section: Introductionmentioning
confidence: 99%